Overview of nurse practitioner practice management in the United States and its implications for China (美国开业护士执业管理概况及对我国的启示) - ZHANG Xiaoman (张小曼); ZHOU Shuping (周淑萍); WANG Xiaomei (王小梅); GUO Chunmei (郭春梅); WANG Chao (王超); WAN Kena (万克娜) (Journal of International Translational Medicine Limited, 2024)
By providing systematic and comprehensive care services, a nurse practitioner play a crucial role in improving quality of primary healthcare and addressing the shortage of general practitioners. This paper provides an overview of the current practice situation, education system, registration certification, and license management of nurse practitioners in the United States. It aims to offer reference for establishing a qualification certification and evaluation management system with Chinese characteristics for nurse practitioners, as well as for educational management. This is of significant practical importance for promoting the cultivation of high-level nursing talents that meet the needs of China's health care development. (开业护士通过提供系统化和全面的护理服务, 在提高初级医疗质量、解决全科医生短缺问题方面发挥重要作用。本文综述了美国开业护士的发展现状、教育体系、注册认证及执业管理, 对高质量的培训体系和持续再认证机制进行分析, 旨在为建立具有中国特色的开业护士资格认证及评价管理体系提供参考。)